#### Answer

$$f(x)=(x^2+2x)e^{x} =2x+3x^2+2x^3+\frac{5x^4}{6}+\frac{x^5}{4}+...$$
Convergent for any value of $x$.

#### Work Step by Step

By making use of Table 2, we have the Maclaurin series for
$f(x)=e^x$ as follows
$$f(x)=e^x=1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+\frac{x^4}{4!}+...$$ Now by the comparison with the function $f(x)=(x^2+2x)e^{x}$, we have the Maclaurin series as follows
$$f(x)=(x^2+2x)e^{x}\\ =(x^2+2x)(1+x+\frac{x^2}{2!}+\frac{x^3}{3!}+\frac{x^4}{4!}+...)\\ =2x+3x^2+2x^3+\frac{5x^4}{6}+\frac{x^5}{4}+...$$ Moreover, again from Table 2, the Maclaurin series for $f(x)=e^x$ is convergent for any value of $x$. Hence, the Maclaurin series for $f(x)=(x^2+2x)e^{x}$ is also convergent for any value of $x$.